Spectral Transmittance of Selected Tinted Ophthalmic Lenses - Chou, B R; Cullen, A P (Canadian Journal of Optometry, 1983)
Spectral transmittance data over the waveband 200 to 2500 nm are presented for a selection of tinted ophthalmic lenses. Criteria for the prescription of tinted lenses are briefly discussed.